2005
DOI: 10.1097/01.wnf.0000152623.46474.07
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate Versus Fluvoxamine in the Treatment of Pathological Gambling

Abstract: Pathologic gambling (PG) is a highly prevalent and disabling impulse control disorder. Recent studies have demonstrated that PG patients respond well to treatment with SSRIs, mood stabilizers, and opioid antagonists. These findings support the idea that PG and other disorders of impulse control may be conceptualized as part of the obsessive-compulsive spectrum disorders. Pilot studies have shown topiramate to be effective in the treatment of specific disorders of impulse control. The aim of the study is to com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(63 citation statements)
references
References 23 publications
1
60
0
2
Order By: Relevance
“…This observation is in line with observations on topiramate's effects on various addictive and/or compulsive behaviors such as alcohol addiction [6], nicotine addiction [7], sexual compulsive behavior [8], pathological gambling [9] as well as binge-eating disorder [10]. It could be of high interest to investigate the importance of automatic and conditioned processes in overeating in obese patients who probably could have better response to topiramate treatment.…”
supporting
confidence: 66%
“…This observation is in line with observations on topiramate's effects on various addictive and/or compulsive behaviors such as alcohol addiction [6], nicotine addiction [7], sexual compulsive behavior [8], pathological gambling [9] as well as binge-eating disorder [10]. It could be of high interest to investigate the importance of automatic and conditioned processes in overeating in obese patients who probably could have better response to topiramate treatment.…”
supporting
confidence: 66%
“…Others have investigated the effectiveness of various prevention (Ferland et al, 2005) and treatment (Dannon et al, 2005;Saiz-Ruiz et al, 2005) programs. One potential risk factor for problematic gambling is alcohol use, but past studies of this relationship have not addressed the potential endogeneity of alcohol use in the gambling equations and/or had minimal generalizability.…”
Section: Introductionmentioning
confidence: 99%
“…36 This study was small and of relatively short duration. In a small case series of 3 kleptomanic patients, it was reported that subjects responded well to topiramate given either alone or in combination with an SSRI.…”
Section: Disorders Of Impulse Controlmentioning
confidence: 99%